Comparative Study of Crude Oil Dehydration Equipments (University of Khartoum Engineering Journal, 2022)
The present study addresses all facets of an efficient, compact and environmentally acceptable crude oildehydration operation based on three different equipments. The equipments considered for the purpose of thisresearch are a gravity settler (liquid-liquid) separator, heater-treater system and electrostatic coalescer. Casestudies present the effect of crude oil properties and operating conditions on the right decision of equipmentselection. The selection is based on mathematical equations that characterize the choices of the separation systemthrough the determination of the required size and expected efficiency. The results of this study showed that thegravity settler is most suitable for dehydration of light density (less than 850 kg/m3) and low water-cut (less than40%) crudes. The heater-treater system is found to be most suitable when dehydration of viscous and high watercut crudes is considered. Furthermore the study concludes that the electrostatic coalescer is most suitably used fordehydration of crude oil with water cut 20% or less, as expected, because short circuiting occurs above this limit;In the cases where crude water cut is less than 20%, the electrostatic coalescer showed the highest expectedefficiency with the lowest equipment size requirements